Perancangan Branding Serta Penerapan Digital Marketing UMKM Catering Ngudi Sempulur Kelurahan Panggungrejo Kab. Tulungagung - Satriyono, Gandung; Rukmini, Meme; Prastiwi, Edwina; Kristanti, Nabilla Deva (LPPM Universitas Bumigora, 2023)
UMKM Catering Ngudi Sempulur which is located in Panggungrejo Village, Tulungagung District, Tulungagung Regency. Catering Ngudi Sempulur has a characteristic that is highlighted from its products that have the taste of the archipelago ontentic race, with a combination of flavors that are in accordance with the tastes of the majority of Indonesians, the ingredients used are fresh and high-quality selected ingredients so that the results have a delicious taste. However, this MSME is considered a pioneering business and requires significant developments in business continuity. Brand awareness in this business is very low and lacks knowledge about digital marketing. The solution carried out is innovation in product packaging and new logos made more attractive and carry out marketing development by creating social media accounts so that MSMEs can be widely known so that they can help business development.